2006
DOI: 10.1063/1.2389019
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of water cluster ions from the surface of solid rare gases

Abstract: Electron or photon irradiation on H 2 O adsorbed on the surface of rare gas solids induces the desorption of protonated water clusters, (H 2 O) n H + . The yield and the size n distribution of cluster ions depend on the coverage, the deposition temperature of water and the thickness of a rare gas film. These results indicate that the (H 2 O) n H + ions are originated from the isolated water cluster and most important factor determining the size n distribution of desorbed (H 2 O) n H + is the sizes of water isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Desorption of protonated clusters from water ice by core-excitation was reported before [48]. It has also been observed and studied in the case of electron [49,14] and ion [50,51] irradiation, as well as in field-assisted photon-stimulated desorption [52] or electron and UV photon stimulated desorption from water adsorbed on rare-gas solids [53,54,55].…”
Section: Desorption Of Protonated Clustersmentioning
confidence: 81%
“…Desorption of protonated clusters from water ice by core-excitation was reported before [48]. It has also been observed and studied in the case of electron [49,14] and ion [50,51] irradiation, as well as in field-assisted photon-stimulated desorption [52] or electron and UV photon stimulated desorption from water adsorbed on rare-gas solids [53,54,55].…”
Section: Desorption Of Protonated Clustersmentioning
confidence: 81%
“…the ESID of pure water ice. [35][36][37][38][39] Moreover, the other members of the water cluster ion series (H 2 O) n + and (H 2 O) n H + with n Z 2 are absent, 40,41 probably because water molecules are well diluted on the frozen CH 3 CN surface. In this framework, Mejı ´as et al 42 showed that a single proton tends to stay bonded to H 2 O to form H 3 O + when solvated by more than one CH 3 CN molecule.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanism based on inter-atomic charge transfer leading to Coulomb repulsion between neighboring ions has been proposed to account for ion desorption induced by electronic transitions (DIET) from the surface of rare gas solids [27]. Recent studies have reported low-energy electron-or photon-stimulated desorption by Coulomb repulsion of large cluster ions (n 8) from molecules adsorbed on condensed gas solids [28][29][30][31]. However, the results in figure 2(a) show that the monomer peak dominates and that only very small cluster ions are observed (n < 5).…”
Section: Mass Spectramentioning
confidence: 99%